Reducción de cr (vi) a cr (iii) por fotocatálisis en presencia de zno y radiación solar. - Gonzáles Mendieta, Freddy George (2013)
Its studied the photoreduction of hexavalent chromium in aqueous medium was studied with zinc oxide (ZnO) in the presence of radiation solar.Se tests performed using solutions of Cr (VI) from K2Cr2O7. These solutions were irradiated with sunlight in the presence of ZnO by 75 min and continued stirring. The variables studied were: concentration of Cr (VI), exposure time, concentration of ZnO, solar radiation, and agitation system. The results show a 100% reduction of Cr (VI) to Cr (III) in 75 minutes is reached. Degradation of Cr (VI) is a function of its concentration, presenting two different behaviors: an exponential and one linear. Also high concentrations of Cr (VI) shielding create problems for ZnO. The percentage reduction of Cr (VI) is proportional to the light intensity solar.Se proposes an equation that relates the reduction rate Cr (VI) with the catalyst concentration.